Field survey to identify the nematode infections on olives seedlings and trees in Baghdad, Babylon and Karbala / IRAQ - Ismail, Waref M. H.; Abdel rasool, Asmaa M.; Altememe, Zeinab A. M. (Journal of Kerbala for Agricultural Sciences, 2018)
The study was aimed to conduct a field survey to identify the plant parasitic nematodes associated with olive trees and nurseries in provinces of Baghdad / Al- Zaafaraniya, Babil /Al- Sada, Karbala /Al-Atishi and Al-Hindiah‎ Horticulture Center. Four genera of nematodes were detected on olives trees and seedlings: root-knot nematodes ‎Meloidogyne spp., the citrus nematode Tylenchulus semipenetrans, reniform nematodes Rotylenchus reniformis and the dagger nematode Xiphinema spp. The last two genera are considered to be recorded as first time on olives trees in Iraq. Root-knot nematodes was the most frequent with ratio 87.7% , observed in all study areas followed by T. semipenetrans and R. reniformis only in the province of Babylon with ratio 9% and 3% respectively. While, Xiphinema spp. was detected only in Karbala specifically in the Al-Atishi area with ratio 3%. Disease incidence and severity of infection with root-knot nematode were recorded in fields and nurseries. Baghdad /Al- Zaafaraniya had the highest percentage of disease incidence (100%) and severity (3) in the field, while nurseries under shade conditions in the same region had the least percentage of disease incidence and severity (6.6%) , (0) respectively.